Shadow dancer [videorecording (DVD)] - Anderson, Gillian, 1968-; Owen, Clive; Gillen, Aidan, 1968-; Riseborough, Andrea, 1981-; Marsh, James, 1963- (Magnolia Home Entertainment, 2013)
"When single mother Collette McVeigh ... is arrested for her part in an aborted IRA plot in London, an MI5 officer ... offers her a choice: lose everything and go to prison or return to Belfast to spy on her own family. With her son's life in her hands, Collette chooses to place her trust in the MI5 and return home. When her brothers' secret operation is ambushed, suspicions of an informant are raised and Collette finds both herself and her family in grave danger"--Container.